Comparison of the primary stability of porous tantalum and titanium acetabular revision constructs - Beckmann, Nicholas A.; Bitsch, Rudi G.; Schonhoff, Mareike; Siebenrock, Klaus-Arno; Schwarze, Martin; Jäger, Sebastian (Materials, 2020)
Adequate primary stability of the acetabular revision construct is necessary for long-term implant survival. The difference in primary stability between tantalum and titanium components is unclear. Six composite hemipelvises with an acetabular defect were implanted with a tantalum augment and cup, using cement fixation between cup and augment. Relative motion was measured at cup/bone, cup/augment and bone/augment interfaces at three load levels; the results were compared to the relative motion measured at the same interfaces of a titanium cup/augment construct of identical dimensions, also implanted into composite bone. The implants showed little relative motion at all load levels between the augment and cup. At the bone/augment and bone/cup interfaces the titanium implants showed less relative motion than tantalum at 30% load (p < 0.001), but more relative motion at 50% (p = n.s.) and 100% (p < 0001) load. The load did not have a significant effect at the augment/cup interface (p = 0.086); it did have a significant effect on relative motion of both implant materials at bone/cup and bone/augment interfaces (p < 0.001). All interfaces of both constructs displayed relative motion that should permit osseointegration. Tantalum, however, may provide a greater degree of primary stability at higher loads than titanium. The clinical implication is yet to be seen
Gesehen am 03.06.2020